Participatory evaluation and promotion of cereals and grain legumes for enhancing food security at Bajura district, Nepal - Neupane, RK; Mahato, BP; Darai, R; Hamal, B (Agronomy Journal of Nepal, 2013)
Participatory varietal selection (PVS) trials in maize, wheat, finger millet, buckwheat, pigeon pea and field pea, mixed cropping legumes with maize were implemented and farmer-preferred varieties of those crops disseminated in Barabish VDC (900-1600 m) of Bajura district during 2007/08 to 2009/10 with a view to enhance the local level food security. Results from PVS trials showed that maize variety Deuti produced the highest mean grain yields of 3625 kg/ha which was 25% higher than the local variety, wheat variety WK-1204 was the highest yielder (3901 kg/ha), with 48% more yields than the popular and check variety RR-21. Fingermillet variety KK -1 was the highest yielder (2459 kg/ha) in midhills, whereas ACC # 2827-1, NF1703-34, and performed better in high hills. This variety showed wider adaptation both in the mid and high hills. Sweet buckwheat genotype IR-13 was most preferred by farmers. For bitter buckwheat, genotypes ACC #- 2223-1 (4813 kg/ha), Sample # 8 (2333 kg/ha) and ACC # -2227-1 (1354 kg/ha) were high yielding. Field pea variety Sikkime produced the highest fresh pod yield of 4185 kg/ha and was superior to Kalaam Local. Seed yields of medium duration pigeonpea variety Rampur Rahar-1 evaluated for the first time in the locality, ranged between 250-1500 Kg/ha. Extra short duration variety of pigeonpea suitable for growing in pigeonpea-wheat rotation in rainfed uplands has been selected by farmers. The economic benefit of intercropping groundnut with maize was higher than intercropping pigeonpea or soybean, due to higher selling price of groundnut. On-farm seed saving and seed procurement of selected varieties had been initiated to ensure adequate seed supply at the local level. More than 1829 kg seed of wheat variety WK-1204 was produced and 40 % of it was used as seed in 2010 winter season. A total of 328 farmers comprising 28% females and 72% males were benefited through participation in crop and seed production trainings organized at the villages. Up-scaling of selected varieties / technologies has been suggested. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7522 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.75-87